Comparative biochemical evolution during ripening of bovine, ovine and caprine cheeses manufactured with extracts of flowers of Cynara cardunculus - Sousa, Maria J. (2011)
Changes in the main physicochemical and biochemical characteristics of bovine, ovine and caprine milk cheeses manufactured with aqueous extracts of flowers of Cynara cardunculus were studied throughout ripening (0 – 68 days). At the end of ripening the pH in the centre was (mean ± ISD) 5.05±0.07, 5.15±0.21 and 4.91±0.07 for bovine, ovine and caprine milk cheeses, respectively; whereas the pH at the top of the cheese was 5.21±0.09, 5.44±0.12 and 5.12±0.07, respectively; the moisture content values of bovine, ovine and caprine milk cheeses were 37.68±2.32, 40.23±4.34 and 45.73±1.44%, respectively; the NaCl content values were 4.00±0.43, 4.00±0.56 and 4.08±0.58 (%TS); the fat content values were 41.01±5.32, 63.60±7.80 and 45.14±9.14 (%TS); the protein content values were 28.96±1.84, 22.89±2.37 and 30.02±1.22 (%TS); the water-soluble nitrogen values were 32.91±1.76, 46.44±1.86 and 48.72±1.08 (%TN); the values of nitrogen soluble in trichloroacetic acid were 10.25±1.93, 10.41±2.91 and 7.25±0.84 (%TN); the values of nitrogen soluble in phosphotungstic acid were 1.50±0.18, 1.87±0.65 and 1.38±0.32 (%TN); finally, the free amino acid content values were 21.33±5.34, 17.51±5.08 and 23.93±4.80 μM equivalents of leucine. Urea-polyacrylamide gel electrophoresis of water-insoluble fractions from cheeses indicated high degrees of proteolysis of αs1-casein in bovine cheeses and more extensive proteolysis of the αs-casein region in caprine than in ovine cheeses, but a moderate degree of proteolysis of β-casein in all types of cheese; electrophoregrams of the water-soluble fraction displayed increasing numbers of bands throughout ripening, an observation that is consistent with the increase in the ratio of water-soluble nitrogen to total nitrogen.